ANALISIS KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA KELAS V SDN 03 PONTIANAK KOTA - Dara Dalilah; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
This research aims to describe the skills of fifth grade students at SDN 03 Pontianak Kota in writing descriptive essays. The method used in this study is a qualitative descriptive method. This study focuses on aspects of neatness, appropriateness of title and content, accuracy between sentences, and choice of words/diction. The source of the data for this research was taken from 29 students in class VB of State Elementary School 03 Pontianak City. This study uses interview instruments, documentation, reading and note-taking techniques. The results of this study show that the average ability to write descriptive essays of students is 72.25 in the (enough) category. This can be seen from the percentage of students who scored in the very good category 9 people or 32.14%, good category 4 people or 14.29%, enough category 11 people or 39.29%, less category 3 people or 10.71% , and very less 1 person or 3.57%. Thus, it can be concluded that the ability to write descriptive essays for class VB students is in the sufficient category because there are still some difficulties faced by students in writing descriptive essays. Keywords: Writing skill, Essay, Description